Brain and Serum Androsterone Is Elevated in Response to Stress in Rats with Mild Traumatic Brain Injury - Servatius, Richard J.; Marx, Christine E.; Sinha, Swamini; Avcu, Pelin; Kilts, Jason D.; Naylor, Jennifer C.; Pang, Kevin C. H. (Frontiers in Neuroscience, 2016)
Exposure to lateral fluid percussion (LFP) injury consistent with mild traumatic brain injury (mTBI) persistently attenuates acoustic startle responses (ASRs) in rats. Here, we examined whether the experience of head trauma affects stress reactivity. Male Sprague-Dawley rats were matched for ASRs and randomly assigned to receive mTBI through LFP or experience a sham surgery (SHAM). ASRs were measured post injury days (PIDs) 1, 3, 7, 14, 21 and 28. To assess neurosteroids, rats received a single 2.0 mA, 0.5 s foot shock on PID 34 (S34), PID 35 (S35), on both days (2S), or the experimental context (CON). Levels of the neurosteroids pregnenolone (PREG), allopregnanolone (ALLO), and androsterone (ANDRO) were determined for the prefrontal cortex, hippocampus and cerebellum. For 2S rats, repeated blood samples were obtained at 15, 30 and 60 min post-stressor for determination of corticosterone (CORT) levels after stress or context on PID 34. Similar to earlier work, ASRs were severely attenuated in mTBI rats without remission for 28 days after injury. No differences were observed between mTBI and SHAM rats in basal CORT, peak CORT levels or its recovery. In serum and brain, ANDRO levels were the most stress-sensitive. Stress-induced ANDRO elevations were greater than those in mTBI rats. As a positive allosteric modulator of gamma-aminobutyric acid (GABA)A receptors, increased brain ANDRO levels are expected to be anxiolytic. The impact of brain ANDRO elevations in the aftermath of mTBI on coping warrants further elaboration.